Understanding menstrual characteristics from the perspective of reproductive energetics: a study on the adolescent Oraon tribal populations - Thakur, Joyeeta; Goswami, Monali; Roy, Subho (Anthropological Review, 2020)
The energetic costs of ovarian functions rely on the oxidizable fuels synthesized from carbohydrate, protein and fat that contribute to body’s fat storage. Energy deficient diet in association with low body fat may disrupt normal ovulatory function and lead to several menstrual irregularities. We examined the association of nutritional status with menstrual characteristics among a group of adolescent Oraon tribal population of West Bengal, India. We selected 301 adolescent girls, aged 10-19 years. Information on socio-demographic status, menstrual characteristics and assessment of the dietary intake and nutritional status were collected following standard protocol. ‘Healthy weight’ participants more likely reported irregularity in periods and skipping of menstrual cycle and shorter cycle length. Multivariate analysis revealed PBF has inverse association with PMS, duration of discharge and skipping of cycle (p